The Role of Games Motivation Young Learner in English Classroom - Amirul, Bani; Hasibuan, Indra Mora (Invention: Journal Research and Education Studies, 2025)
The Role of Games is able to improve English learning for Young Learners. This paper explores the use of games as an instructional strategy to enhance motivation among young learners in English classrooms. This paper aims to increase the motivation to learn English using the game method. Data information is collected from reliable sources as analytical material. From the discussion, it can be concluded that English must be taught from an early age due to the impact of globalization and English becoming an international official language. Learning English A in early childhood is carried out by role-playing so that children do not feel bored and enthusiastic in learning English. The Role of Games is carried out by developing the involvement of young students to be more active in learning. Role-playing makes it easier for young students to remember the content of English learning. This learning model is an activity dedicated to young learners in developing English language skills. The use of The Role of Games learning model is able to create a fun learning atmosphere. The findings suggest that games can significantly increase student engagement, improve language acquisition, and create a positive learning environment. So that it can be used as motivation to facilitate the understanding of learning content.